Predicting the Direction of the Lq45 Stock Market in Indonesia - Curie Nabilah Nasution (Syntax Literate, 2023)
To cope with the unpredictability of the stock market, investors should have a solid understanding of the ups and downs of bullish and bearish phases. This is especially true when looking at Indonesia's LQ45 index, which consists of 45 of the most liquid stocks in Indonesia. This study carefully predicts the future direction of movement of the LQ45 stock price index by first figuring out its bearish and bullish periods, and then finding important macroeconomic factors. In this study, techniques such as X13 ARIMA SEATS, Bry-Boschan, and Binomial Logistic Regression are used to find clear bullish and bearish phases in the LQ45 index time frame. These techniques also point out certain macroeconomic indicators, such as Motor Sales, Retail Sales, Oil Price, BI Rate, 1-month Deposito Rate Working Capital Rate, Rupiah Exchange Rate, Inflation Narrow Money, Broad Money, US PMI Manufacture, and US Inflation, which have a great effect on these market conditions, as indicated by their p-values. Based on these insights, predictive models were created to show how the LQ45 index may change in the future. These models provide asset management companies with a solid basis for making smart investment decisions, with a tendency to be more aggressive when the market is up and more cautious when the market is down. This study is special because it combines the analysis of LQ45 index market trends with important macroeconomic factors in a way that has never been done before in the Indonesian market.